What Does Current Evidence Say About Prenatal Education to Succeed Alquran Hafiz - Abd. Basir; Akhmad Syahbudin; M. Daud Yahya; Armizi Armizi; Fahrina Yustiasari Liriwati (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This study aimed to find scientific evidence of success for parents in preparing Hafiz Al-Quran for an excellent birth or pregnancy period. The authors believe that education in preparing hafid of the Qur'an can be done before birth. For this reason, many published reviews in the form of evidence of scientific studies have been carried out on many national and international publications that discuss the issue of prenatal education for the success of the Hafiz Al-Quran cadre. Data analysis begins with a study of data coding, in-depth evaluation, and drawing conclusions based on evidence that can answer this study question. This study relies entirely on secondary data that we searched electronically. Based on the analysis and criticism of the data, we can conclude that it is true that the study evidence states that education in producing Hafiz Qur'an cadres can also be started when the baby is still in the womb. Thus, these findings should serve as supporting data for similar studies in the future.